2017
DOI: 10.1371/journal.pntd.0005311
|View full text |Cite
|
Sign up to set email alerts
|

Identification of BALB/c Immune Markers Correlated with a Partial Protection to Leishmania infantum after Vaccination with a Rationally Designed Multi-epitope Cysteine Protease A Peptide-Based Nanovaccine

Abstract: BackgroundThrough their increased potential to be engaged and processed by dendritic cells (DCs), nanovaccines consisting of Poly(D,L-lactic-co-glycolic acid) (PLGA) nanoparticles (NPs) loaded with both antigenic moieties and adjuvants are attractive candidates for triggering specific defense mechanisms against intracellular pathogens. The aim of the present study was to evaluate the immunogenicity and prophylactic potential of a rationally designed multi-epitope peptide of Leishmania Cysteine Protease A (CPA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 65 publications
(77 reference statements)
1
28
0
1
Order By: Relevance
“…Notably, 4 months post-infection, the level of protection in the liver ranged from 64% to 92%, speeding up the phenomenon of selfhealing observed in this organ, while vaccination with PLGA nanoformulations resulted in significant parasite reduction, also, in the spleen, ranging from 44% to 99% (Figure 1). Encapsulation of MPLA in PLGA-sLiAg NPs resulted in significant reduction of parasitic load in accordance with previous studies demonstrating the necessity for an adjuvant for experimental vaccines against leishmaniasis [36][37][38][39][40] but also against other intracellular pathogens. 41,42 The conjugation of the p8 peptide to PLGA-sLiAg NPs resulted in protection levels similar to those induced by PLGA-sLiAg-MPLA vaccination.…”
Section: Discussionsupporting
confidence: 91%
“…Notably, 4 months post-infection, the level of protection in the liver ranged from 64% to 92%, speeding up the phenomenon of selfhealing observed in this organ, while vaccination with PLGA nanoformulations resulted in significant parasite reduction, also, in the spleen, ranging from 44% to 99% (Figure 1). Encapsulation of MPLA in PLGA-sLiAg NPs resulted in significant reduction of parasitic load in accordance with previous studies demonstrating the necessity for an adjuvant for experimental vaccines against leishmaniasis [36][37][38][39][40] but also against other intracellular pathogens. 41,42 The conjugation of the p8 peptide to PLGA-sLiAg NPs resulted in protection levels similar to those induced by PLGA-sLiAg-MPLA vaccination.…”
Section: Discussionsupporting
confidence: 91%
“…Based on the immunological findings in the spleen of Cockt-1 immunized mice, we assessed the parasite load in the endpoint to evaluate the efficacy of the peptide cocktails vaccine strategy. Regarding peptide vaccines for leishmaniasis, few studies are reported, and they are in immunogenicity phase with no outcome for parasite load [3][4][5]34,43,44]. Our results demonstrate that Cockt-1 can promote a significant reduction of parasite load in the spleen, which was not observed for Cockt-2.…”
Section: Discussionmentioning
confidence: 53%
“…From the application of such approaches and selection criteria, promising new candidates were proposed. Among them, peptide vaccines, chosen from immunogenic portions of known vaccine candidates such as KMP-11, were tested pre-clinically, often associated with DC-based vaccination strategies or nanosized vaccine-delivery systems [72,94,95]. Interestingly, a recently published work proposes a peptide vaccine candidate (from Leishmania phosphoenolpyruvate carboxykinase-PEPCK) that may be effective for both VL and CL should the results obtained in the pre-clinical context translate into the clinical one [90].…”
Section: Second-generation Vaccine Candidatesmentioning
confidence: 99%